ChemInform Abstract: Borontribromide‐Mediated C—C Bond Formation in Cyclic Ketones: A Transition Metal Free Approach. Issue 5 (February 2015) - Ahmad, Imran; Pathak, Vinay; Vasudev, Prema G.; Maurya, Hardesh K.; Gupta, Atul
Abstract A new application of BBr3 as a C—C bond forming agent in cyclic ketones, tetralones, chromenone, thiochromenone, and indanones, is investigated.